Use of the N,N-dialkyl-N’-benzoyl(thio)selenoureas as single source precursors for the synthesis of semiconducting quantum dots - Bruce, Jocelyn Catherine (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Chemistry and Polymer Science))--Stellenbosch University, 2008.